Effect of Atmospheric Pollutants on the Air Quality in Tunisia - Karim Bouchlaghem; Blaise Nsom (The Scientific World Journal)
This paper presents the evolution of Saharan dust advection when the PM10 (particles with an aerodynamic diameter below 10 μm) concentration exceeds standard limits in different Tunisian sites. Meteorological and concentration data (from 2004 to 2010) obtained from several monitoring stations and in situ measurements were used to identify African dust change in seasonal occurrence, their source origin, and their impact on surface PM10 concentrations. We pointed out that the Saharan dust contribution caused frequently the surpassing of the maximum number of days in excess of EU standard limits as well as of the maximum yearly average in the Mediterranean Tunisian coasts. The maximum daily concentration reaches 439 μg/m3 during the Saharan events. The decrease in particulate levels recorded at the end of each event is due to the injection of European air masses and rainfalls. Primary pollutants peaks were much higher in winter than in summer which can be explained on the basis of the lower ventilation and mixing.